Deliverance - Voight, Jon, 1938-; Reynolds, Burt.; Beatty, Ned.; Cox, Ronny; Boorman, John, 1933-; Dickey, James; Warner Bros.; Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 1999)
Four ordinary men, in two canoes, descending a river they've only seen as a squiggly line on a map, determined to test themselves against a wilderness they only think they understand, must fight for their lives against some sadistic mountain men.
Videodisc release of the 1972 motion picture.
Includes behind-the-scenes documentary: The dangerous world of Deliverance.
Widescreen and standard versions ; remastered in Dolby digital 5.1 ; interactive menus, production notes, theatrical trailer, scene access.
Director of photography, Vilmos Zsigmond ; editor, Tom Priestley.
Jon Voight, Burt Reynolds, Ned Beatty, Ronny Cox.
Rated R.
Keywords: Films for the hearing impaired; Action and adventure films; Wilderness survival -- Drama; Feature films